ANTIAGING PROPERTIES OF CREAM MADE WITH COCOA POLYPHENOL, ALOE VERA (Aloe barbadensis) AND SEAWEED (Euchema cottoni) AS ACTIVE AGENTS Sifat Antiaging dari Krim Berbahan Aktif Polifenol Kakao, Aloe Vera (Aloe barbadensis) dan Rumput Laut (Euchema cottoni) - Eky Yenita Ristanti; Sitti Ramlah; Dwi Indriana (Jurnal Industri Hasil Perkebunan, 2018)
Cream made from cocoa polyphenol combined with aloe vera and seaweed has been prepared and its antiaging properties has been studied. Cream composition consisted of cocoa butter, olive oil, sodium dodecyl sulphate, polypropylene glycol, cetyl alcohol and aquadest as the cream base. Cocoa polyphenol, aloe vera and seaweed were used as active agent to perform antiaging activity. Antiaging tests were done in vivo, using male Wistar rats. Antiaging tests included cream effectivity to protect skin from UV B radiation, which indicated by wrinkle, exfoliation, erythema and skin elasticity. Result of this research shows that skin applied with cream contained cocoa polyphenol, aloe vera and seaweed has less wrinkle and erythema after being exposed with UV B lamp for 2 weeks. Cream contained 3 active ingredients (cocoa polyphenol, aloe vera and seaweed) shows less effectivity to protect against exfoliation compare to cream with only 2 active ingredients (aloe vera and seaweed), however, cream with 3 ingredients still shows better protection to skin, compare to the unprotected skin (skin which not applied with any cream). In addition, skin applied with cream contained cocoa polyphenol, aloe vera and seaweed shows better elasticity, compared to those which not applied with cream.